Variations in precipitation and temperature in Xinjiang (Northwest China) and their connection to atmospheric circulation - Zhou, Guixiang; Chen, Yaning; Yao, Junqiang (Frontiers in Environmental Science, 2023)
As one of the most vulnerable types of global ecosystems and water resource systems, arid regions are most sensitive to climate change. The Xinjiang (XJ) region is an important part of the arid region in Central Asia and is representative of global arid regions. The complex topography and underlying surface result in distinct climate change characteristics in XJ. The change in temperature and precipitation over XJ and its sub-regions were investigated from 1960 to 2019 using the Mann-Kendall method and cross-wavelet analysis. Moreover, the multi-timescale correlations between the variations in temperature and precipitation and the atmospheric circulation indices were explored. The results show significant warming and wetting trends in XJ from 1960 to 2019. The warming rate was 0.32°C/10 a (p<0.01), with an abrupt change during the mid-1990s. The increasing rate of precipitation was 9.24 mm/10 a (p<0.01), with an abrupt change during the middle to late 1990s. In terms of seasonal variation, the greatest warming rate was during winter (0.37°C/10 a), whereas the precipitation increase was concentrated in summer (3.48 mm/10 a). In terms of spatial variation, a significant warming trend was observed in THB, IRB, ILRB, and NSTM, and precipitation increased significantly in ILRB, NSTM, and the western TRB in southern XJ. The Hurst index analysis indicated that the warming and wetting trends in XJ will slow in the future. Climate change in XJ was closely related to atmospheric circulation at multiple timescales. The subtropical high, Northern-Hemisphere polar vortex activities and the Tibetan Plateau have a significant impact on climate change in XJ. The annual mean temperature in XJ was positively correlated with the area and intensity index of the subtropical high over North Africa, Atlantic, and North America , and negatively correlated with the area and intensity index of the Asia polar vortex. The XJ annual precipitation was positively correlated with the index of the Tibet Plateau Region 1 and negatively correlated with the intensity index of the Atlantic and European polar vortex, and the area and intensity index of the Northern Hemisphere polar vortex.